2005
DOI: 10.1207/s15374424jccp3401_10
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Social Information Processing and Their Relations With Reactive and Proactive Aggression in Referred Aggressive Boys

Abstract: We studied emotional aspects of social information processing (SIP) The reformulated social information processing model (SIP;Dodge, 1986) is an important element in theoretical accounts of the development of aggressive behavior. The model proposes that behavioral responses to social situations depend on a sequence of information-processing steps. According to the model, information is encoded and interpreted. Interaction goals are then specified, triggering generation of responses to attain these goals. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
235
3
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(267 citation statements)
references
References 36 publications
20
235
3
9
Order By: Relevance
“…Emotion was measured in terms of arousal reactivity by Williams, Lochman, Phillips, and Barry (2003) who found that moderately aggressive boys exhibited increased heart rate and increased hostile attributions when a threat was introduced. In a test of Lemerise and Arsenio's (2000) theoretical model including emotion, hostile attributions, and aggression, boys' report of their own anger was related positively to their hostile attributions, as well as to their aggression (Orobio de Castro, Merk, Koops, Veerman, & Bosch, 2005). In this same study, boys' interpretation of a peer as appearing angry was related to increased hostile attributions.…”
Section: Hostile Attributions and Emotionmentioning
confidence: 61%
“…Emotion was measured in terms of arousal reactivity by Williams, Lochman, Phillips, and Barry (2003) who found that moderately aggressive boys exhibited increased heart rate and increased hostile attributions when a threat was introduced. In a test of Lemerise and Arsenio's (2000) theoretical model including emotion, hostile attributions, and aggression, boys' report of their own anger was related positively to their hostile attributions, as well as to their aggression (Orobio de Castro, Merk, Koops, Veerman, & Bosch, 2005). In this same study, boys' interpretation of a peer as appearing angry was related to increased hostile attributions.…”
Section: Hostile Attributions and Emotionmentioning
confidence: 61%
“…Therefore, future research regarding negative and aggressive interpretation bias might include more implicit, real life measurements. Thirdly, the reactive aggression scale is part of a self-report questionnaire, which does not evoke emotional responses or cognitions in real life [3]. Future research might focus on more real life provocation methods, for instance using Virtual Reality techniques.…”
Section: Discussionmentioning
confidence: 99%
“…According to the social information-processing model of Crick and Dodge [1][2][3], aggressive behaviour arises from a tendency to interpret other people's intentions as hostile and aggressive. This tendency is also present in ambiguous, non-provoking or threatening situations, were others' intentions are benign [4][5][6].…”
Section: Study 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations